2012
DOI: 10.3732/ajb.1100568
|View full text |Cite
|
Sign up to set email alerts
|

A Lower Cretaceous (Valanginian) seed cone provides the earliest fossil record for Picea (Pinaceae)

Abstract: As an early member of the extant genus Picea, this seed cone extends the fossil record of Picea to the Valanginian Stage of the Early Cretaceous, ca. 136 Ma, thereby resolving a ghost lineage predicted by molecular divergence analyses, and offers new insight into the evolution of Pinaceae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 105 publications
1
48
0
Order By: Relevance
“…The flora includes lycophytes, equisetophytes, several fern families (Smith et al 2003;Hernandez-Castillo et al 2006;Little et al 2006aLittle et al , 2006bRothwell and Stockey 2006;Stockey et al 2006;Vavrek et al 2006;Rothwell et al 2014), as well as numerous gymnosperms (Stockey and Wiebe 2008;Stockey and Rothwell 2009;Klymiuk and Stockey 2012;Rothwell and Stockey 2013;Rothwell et al 2014;Atkinson et al 2014aAtkinson et al , 2014bRay et al 2014), fungi (Smith et al 2004;Bronson et al 2013), a lichen (Matsunaga et al 2013), and numerous bryophytes ).…”
Section: Locality and Floramentioning
confidence: 99%
“…The flora includes lycophytes, equisetophytes, several fern families (Smith et al 2003;Hernandez-Castillo et al 2006;Little et al 2006aLittle et al , 2006bRothwell and Stockey 2006;Stockey et al 2006;Vavrek et al 2006;Rothwell et al 2014), as well as numerous gymnosperms (Stockey and Wiebe 2008;Stockey and Rothwell 2009;Klymiuk and Stockey 2012;Rothwell and Stockey 2013;Rothwell et al 2014;Atkinson et al 2014aAtkinson et al , 2014bRay et al 2014), fungi (Smith et al 2004;Bronson et al 2013), a lichen (Matsunaga et al 2013), and numerous bryophytes ).…”
Section: Locality and Floramentioning
confidence: 99%
“…Much of our understanding of the early evolution and diversity of the family is based on isolated permineralized seed cones from the Cretaceous and Paleogene of Eurasia and North America (reviewed by Miller 1976;Klymiuk et al 2012;Smith et al 2016). These cones are structurally diverse and thought to include both representatives of modern genera and extinct lineages (Miller 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Early Cretaceous seed cones attributed to Picea A. Dietr. and Pinus L. arguably represent the oldest records for extant genera (Alvin 1960;Klymiuk and Stockey 2012;. Pinus arnoldii Klymiuk, Stockey et Rothwell from the Eocene of British Columbia is the only extinct species of Pinaceae with a morphological concept based on a whole-plant reconstruction (Klymiuk et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Paleobotanical studies indicated that Picea would differentiate during middle Jurassic (Zackos et al 2001) and a fossil of P. burtonii was discovered from Early Cretaceous (136 Ma) (Klymiuk and Stockey 2012). In the late Miocene (10-5 Ma) species dispersed over North Hemisphere and species differentiation was presented by molecule data (Lockwood et al 2013).…”
Section: Comparative Analysis Of Cma-banded Karyotype Among Picea Taxamentioning
confidence: 99%